Bank capital structure, regulatory capital, and securities innovations - George Benston; Paul Irvine; Jim Rosenfeld; Jr. Joseph F. Sinkey (Federal Reserve Bank of Atlanta, 2000)
Although financial instruments that, in effect, permit corporations to treat preferred stock dividends as tax-deductible interest have been used by nonfinancial corporations since late 1993, bank holding companies (BHCs) did not issue these trust-preferred securities (TPS) until 1996, when the Federal Reserve qualified them as Tier-1 capital. We delineate and test hypotheses with 1) analyses of the stock-market reaction to the Fed's ruling and to TPS filings and 2) comparisons of BHCs that issued TPS with those that did not. We conclude that regulatory capital requirements, tax savings, and uninsured sources of funds can have significant positive effects on BHCs' demand for capital; growth and investment opportunities have an inconclusive effect; and transaction costs have a negative effect. Our results are not consistent with the moral-hazard hypothesis.
Keywords: 330; Bank capital; Bank holding companies; Bank supervision; Securities